BRCA1-methylated triple negative breast cancers previously exposed to neoadjuvant chemotherapy form RAD51 foci and respond poorly to olaparib - Velazquez, Carolina; Orhan, Esin; Tabet, Imene; Fenou, Lise; Orsetti, Béatrice; Adélaïde, José; Guille, Arnaud; Thézénas, Simon; Crapez, Evelyne; Colombo, Pierre-Emmanuel; Chaffanet, Max; Birnbaum, Daniel; et al. (Frontiers in Oncology, 2023)
Background: About 15% of Triple-Negative-Breast-Cancer (TNBC) present silencing of the BRCA1 promoter methylation and are assumed to be Homologous Recombination Deficient (HRD). BRCA1-methylated (BRCA1-Me) TNBC could, thus, be eligible to treatment based on PARP-inhibitors or Platinum salts. However, their actual HRD status is discussed, as these tumors are suspected to develop resistance after chemotherapy exposure. Methods: We interrogated the sensitivity to olaparib vs. carboplatin of 8 TNBC Patient-Derived Xenografts (PDX) models. Four PDX corresponded to BRCA1-Me, of which 3 were previously exposed to NeoAdjuvant-Chemotherapy (NACT). The remaining PDX models corresponded to two BRCA1-mutated (BRCA1-Mut) and two BRCA1-wild type PDX that were respectively included as positive and negative controls. The HRD status of our PDX models was assessed using both genomic signatures and the functional BRCA1 and RAD51 nuclear foci formation assay. To assess HR restoration associated with olaparib resistance, we studied pairs of BRCA1 deficient cell lines and their resistant subclones. Results: The 3 BRCA1-Me PDX that had been exposed to NACT responded poorly to olaparib, likewise BRCA1-WT PDX. Contrastingly, 3 treatment-naïve BRCA1-deficient PDX (1 BRCA1-Me and 2 BRCA1-mutated) responded to olaparib. Noticeably, the three olaparib-responsive PDX scored negative for BRCA1- and RAD51-foci, whereas all non-responsive PDX models, including the 3 NACT-exposed BRCA1-Me PDX, scored positive for RAD51-foci. This suggested HRD in olaparib responsive PDX, while non-responsive models were HR proficient. These results were consistent with observations in cell lines showing a significant increase of RAD51-foci in olaparib-resistant subclones compared with sensitive parental cells, suggesting HR restoration in these models. Conclusions: Our results thus support the notion that the actual HRD status of BRCA1-Me TNBC, especially if previously exposed to chemotherapy, may be questioned and should be verified using the BRCA1- and RAD51-foci assay.